Enterprise information security risks: a systematic review of the literature - Jenner Lavalle Sandoval; Domingo Hernández Celis; Michael Cabanillas-Carbonell; Laberiano Andrade-Arenas (Institute of Advanced Engineering and Science, 2023)
Currently, computer security or cybersecurity is a relevant aspect in the area of networks and communications of a company, therefore, it is important to know the risks and computer security policies that allow a unified management of cyber threats that only seek to affect the reputation or profit from the confidential information of organizations in the business sector. The objective of the research is to conduct a systematic review of the literature through articles published in databases such as Scopus and Dimension. Thus, in order to perform a complete documentary analysis, inclusion and exclusion criteria were applied to evaluate the quality of each article. Then, using a quantitative scale, articles were filtered according to author, period and country of publication, leaving a total of 86 articles from both databases. The methodology used was the one proposed by Kitchenham, and the conclusion reached was that the vast majority of companies do not make a major investment in the purchase of equipment and improvement of information technology (IT) infrastructure, exposing themselves to cyber-attacks that continue to grow every day. This research provides an opportunity for researchers, companies and entrepreneurs to consult so that they can protect their organization's most important assets.